Tribo-Mechanisms of Carbon Nanotubes: Friction and Wear Behavior of CNT-Reinforced Nickel Matrix Composites and CNT-Coated Bulk Nickel - Leander Reinert; Sebastian Suárez; Andreas Rosenkranz (Lubricants, 2016)
In this study, nickel matrix composites reinforced by carbon nanotubes (CNTs) are compared to unreinforced CNT-coated (by drop-casting) bulk nickel samples in terms of their friction and wear behavior, thus gaining significant knowledge regarding the tribological influence of CNTs and the underlying tribo-mechanism. It has been shown that the frictional behavior is mainly influenced by the CNTs present in the contact zone, as just minor differences in the coefficient of friction between the examined samples can be observed during run-in. Consequently, the known effect of a refined microstructure, thus leading to an increased hardness of the CNT reinforced samples, seems to play a minor role in friction reduction compared to the solid lubrication effect induced by the CNTs. Additionally, a continuous supply of CNTs to the tribo-contact can be considered isolated for the reinforced composites, which provides a long-term friction reduction compared to the CNT-coated sample. Finally, it can be stated that CNTs can withstand the accumulated stress retaining to some extent their structural state for the given strain. A comprehensive study performed by complementary analytical methods is employed, including Raman spectroscopy and scanning electron microscopy to understand the involved friction and wear mechanisms.